Evolution and function of calponin and transgelin - Hsieh, Tzu-Bou; Jin, J.-P. (Frontiers in Cell and Developmental Biology, 2023)
Calponin and transgelin (originally named SM22) are homologous cytoskeleton proteins that regulate actin-activated myosin motor functions in smooth muscle contraction and non-muscle cell motility during adhesion, migration, proliferation, phagocytosis, wound healing, and inflammatory responses. They are abundant cytoskeleton proteins present in multiple cell types whereas their physiological functions remain to be fully understood. This focused review summarizes the evolution of calponin and transgelin and their isoform genes and discusses the structural similarity and divergence in vertebrate and invertebrate species in the context of functions in regulating cell motility. As the first literature review focusing on the evolution of the calponin-transgelin gene family in relevance to protein structure-function relationship, the goal is to outline a foundation of current knowledge for continued investigations to understand the biological functions of calponin-transgelin family proteins in various cell types in physiological and pathological processes.